شیخ عابد سندھی اور ان کا علمی مقام ومنہج : "طوالع الانوار "کی روشنی میں ایک مطالعہ (Al-Qamar, 2019)
This article studies Sheikh ʻAbid Sindhī (1776-1841), a renowned Ḥanafī scholar and Ḥadīth expert of Sindh, and his scholarship in the light of “Ṭawaliʻ al-Anwār”, a commentary by Sindhī on Ḥanafī school’s prominent treatise “al-Durr al-Mukhtār”. The Study finds that Sheikh ʻAbid Sindhī had a perfect access to the sciences of Ḥadīth, ʻĪlm al-Rijāl and jurisprudence.  He collected precious Knowledge from Quran, Ḥadīth and books of the jurists. “Ṭawaliʻ al-Anwār” is an encyclopedia of Ḥanafī jurisprudence and a masterpiece of his scholarly research on jurisprudential details. This great book needs the attention of the scholars and researchers to be studied and annotated in a decorous manner so that the people continue to benefit from this great work.
Keywords: Sheikh ʻAbid Sindhī; jurisprudence; “Ṭawaliʻ al-Anwār”